Citra Maskulinitas dalam Novel Laki-Laki Tanpa Tanya Karya Isma’ul Ahmad - Anggraeni Kartika Sari; Onok Yayang Pamungkas; Eko Sri Israhayu; Mulasih Mulasih; Akhmad Fauzan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Masculinity standards make men limited in expressing their expressions. This can lead to identity crises and depression. For this reason, the purpose of this research is to describe the image of masculinity, as well as to find out the impact of masculinity for the characters in the novel Laki -Laki Tanpa Tanya by Isma'ul Ahmad. The source of data in this study is the novel Laki -Laki Tanpa Tanya by Isma'ul Ahmad. The research data is in the form of text in the novel Laki Tanpa Tanya by Isma'ul Ahmad. This research uses the hermeneutic method. Meanwhile, for the data collection technique, it uses the reading and recording technique. Data validity uses theoretical triangulation. Researchers associate various theoretical views so that the results of data analysis are not biased (Cresswell, 2009) Analysis techniques use theories from Miles and Huberman which have three stages, namely; (1) Data reduction; (2) Data presentation; (3) Verification and withdrawal of Conclusions. The findings of this study are the novel Men Without Questions by Isma'ul Ahmad, there are 15 images of masculinity, including: (1) Hard Worker; (2) Protector; (3) Compassionate; (4) Educators; (5) Brave; (6) Concern; (7) Breadwinners; (8) Rebels; (9) Leaders; (10) Never give up; (11) Strength; (12) Discipline; (13) Emotional; (14) Fighters; (15) Violence. Meanwhile, the impact of masculinity on the characters is the impact of sissy masculinity and macho masculinity. Research can provide understanding and raise people's thinking levels towards the formation of masculinity images and social dynamics that will have an impact when socializing in society. In addition, this research can also help educational institutions in developing curricula and learning programs that are more comprehensive and sensitive to gender issues